Boron carbonitride (BxCyNz) nanosheets based single electrode triboelectric nanogenerator for wearable UV photodetectors. (February 2023) - Bayan, Sayan; Pal, Sourabh; Ray, Samit K.
Highlights: Fabrication of boron carbonitride (Bx Cy Nz ) nanosheet based single electrode triboelectric nanogenerator (STENG) on wearable textile. Ultraviolet (UV) photodetection using the STENG during biomechanical movement with remarkable photoresponsivity of 1.6 × 10 3  V/W. Understanding the photodetection mechanism through photoinduced increment of inherent capacitance. Demonstration of signal transmission of the device for potential application as futuristic wearable photodetector. Abstract: Exposure to intense UV radiation is a life threatening issue for the Military personals posted at high altitude. We report on the first ever fabrication of boron carbonitride (Bx Cy Nz ) nanosheets based single electrode triboelectric nanogenerator (STENG) on wearable textile platform for ultraviolet (UV) photodetection. The 2D nature of the Bx Cy Nz samples has been revealed from the microscopy-based characterization tools, while the UV absorption ability of the material has been analyzed using UV-visible absorption spectroscopy. During biomechanical action, the UV detection using the STENG can be realized by the event of lowering of output voltage under UV illumination. The observation of excellent photoresponsivity ∼ 1.6 × 10 3 V/W can be assigned to the nitrogen deficient microstructures of Bx Cy Nz, offering trap states to facilitate electron-hole pair dissociation and their subsequent separation. However, the basic mechanism of photodetection relies on the increment of the inherent capacitance as a consequence photoexcitation in Bx Cy Nz . As a significant outcome of this process, the output voltage of a load capacitor is found to be elevated under illumination and thus turns out to be an alternative method of photodetection. Finally, the photodetection characteristics and the signal transmitting ability of the STENG have been demonstrated upon attaching it to the human body. Thus, Bx Cy Nz based STENG demonstrating photodetection through capacitive voltage growth can form as the basis of next generation flexible, smart and self-powered photodetectors. Graphical abstract: Image, graphical abstract